2022
DOI: 10.3390/min12010078
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Aggregate Production Circuit through Modeling of Crusher Operation

Abstract: The paper concerns investigation of the effect of impact crusher operation on selected qualitative characteristics of mineral aggregate products. Qualitative characteristics of crushing products in terms of size reduction ratio and fine particles contents were analyzed from the point of view of operational parameters of the impact crusher. An investigative program was carried out on a plant scale and two primary parameters of the impactor were analyzed: velocity of the crusher rotor and the width of the outlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Furthermore, experimental methods make it difficult to observe the crushing process of individual particles due to equipment limitations . Hence, to surmount the constraints of empirical investigation and gain a more comprehensive understanding of the evolution mechanism and overall mechanical characteristics of the particle crushing process. The study used the discrete element method to investigate the crushing characteristics of particles which can discretize the complete particle crushing process, enabling a frame-by-frame analysis of the particle crushing procedure. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, experimental methods make it difficult to observe the crushing process of individual particles due to equipment limitations . Hence, to surmount the constraints of empirical investigation and gain a more comprehensive understanding of the evolution mechanism and overall mechanical characteristics of the particle crushing process. The study used the discrete element method to investigate the crushing characteristics of particles which can discretize the complete particle crushing process, enabling a frame-by-frame analysis of the particle crushing procedure. , …”
Section: Introductionmentioning
confidence: 99%
“…21−23 The study used the discrete element method to investigate the crushing characteristics of particles which can discretize the complete particle crushing process, enabling a frame-by-frame analysis of the particle crushing procedure. 24,25 In addition, in terms of DEM simulation of single particle impact crushing, Ueda et al studied the disintegration damage of spherical and ellipsoidal particles using DEM. The results indicated that only slender particles can undergo bending fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feed parameters (grain size, mass, moisture, rock mechanical properties), the method of filling the crusher, the shape of the working parts, the speed of movement, grate gaps and other parameters all influence the output material. In the case of simple crushers, with jaw or cone, where the gap size and the working frequency can be changed, several mathematical models allow estimations of the efficiency and grain size of the crushed product [1][2][3].…”
Section: Introductionmentioning
confidence: 99%